Site-level strategies for managing secondary forests - Sabogal, C. (ITTO, 2005)
This chapter sets out the possible management objectives and technical options for managing secondary forests as part of an forest landscape rehabilitation (FLR) program. The two main alternative strategies – managing improved fallows without compromising agricultural production, and managing forests for production or conservation purposes – are discussed, together with the types of conditions that favour one above the other. There is considerable ambiguity and confusion in the current use of the term ‘secondary forest’ both in the literature and in people’s perceptions. The term has been applied to numerous types of forests with different characteristics and arising from many different processes. ITTO (2002) defines it as: woody vegetation regrowing on land that was largely cleared of its original forest cover (ie carried less than 10% of the original forest cover).